G458(P) Would a genetic panel be able to elucidate the cause of a child presenting with severe chronic kidney disease in the near future? a population survey of existing mutations. (24th May 2017) - Naples, R; Yates, L; Johnson, S; Ognjanovic, M; Tse, Y
Abstract : Aims: To determine the prevalence of diagnostic genetic mutations in all children with chronic kidney disease (CKD) stage 3A in a defined UK population. Methods: All children £18 years with CKD stage 3A in a UK region with total population 3.2m in 2016 were included. Phenotype data was obtained from patient clinical records, and previous investigations identified from hospital records and the regional genetics database. Results: 68 children with CKD 3A were identified in our region (1 in 10 000 children). 33/68 (49%) have had genetic investigations performed. A diagnostic genetic abnormality was identified in 14/33 (42%) of those investigated. 2/33 (6%) had mutations of uncertain significance. Patients were more likely to have undergone genetic investigations if they had associated extra-renal diagnoses (66% vs 27%). No association was found between investigation and patient age or CKD severity. Diagnostic genetic mutations were most commonly found in children in the syndromic non-CAKUT (congenital anomalies of the kidney and urinary tract) group (see table). A diagnostic genetic change was present in 2/20 (40%) patients with a condition not identifiable on ultrasound scan, and a combination of ultrasound and genetics revealed a diagnosis in 56/68 (82%) children. Conclusion: The combined use of genetic investigations and ultrasound scan has a high diagnostic yield in children with CKD. Accurate diagnosis of primary renal disease may not possible for late presenters but is important to determine disease recurrence risk for transplantation. As whole exome sequencing becomes cheaper, quicker and more accessible, designing a panel as an early non-invasive investigation in children with CKD seems logical.